EFISIENSI SERAPAN S DAN HASIL PADI DENGAN PEMBERIAN PUPUK KANDANG PUYUH DAN PUPUK ANORGANIK DI LAHAN SAWAH (MUSIM TANAM II) - Hery Widijanto; Noviana Anditasari; Suntoro Suntoro (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2011)
Title : Efficiency of S Up Take and Rice Yield with Quail Manure and Inorganic Fertilizer in Paddy Soil (Season II). The aim of this research was to know the effect of inorganic fertilizer quail manure to efficiency of Sulphur up take and to know treatment combination that give highest rice yield. This research had been done at Palur, Mojolaban, Sukoharjo, started from January until August 2008. This research used factorial experiment that arranged in Randomized Complete Block Design (RCBD) with two factors. The first factor was 3 levels of inorganic fertilizer dosage i.e.: without inorganic fertilizer, 50% recommendation dosage and 100% recommendation dosage (urea, ZA, SP‐36 and KCl were 300, 100, 150 and 100 kg. ha‐1). And second factor was 3 levels of quail manure dosage i.e.:0, 3 and 6 ton.ha‐1. Statistical analysis used F test, Duncan’s Multiple Range (DMR) test at 5% in level and Correlation test. The Result of this research showed that, interaction between inorganic and quail manure increased significantly efficiency of S uptake. Dosage quail manure increased significantly total weight of dry hust. The highest efficiency of S uptake was on 100% recommendation dosage inorganic fertilizer and quail manure dosage 3 ton.ha‐1 (44.12%). The highest total weight of dry hust on 50% recommendation dosage inorganic fertilizer and quail manure dosage 6 ton.ha‐1 Key words: quail manure, efficiency of S uptake and paddy soil